Analisis Teknik Deep Focus Dalam Menciptakan Komposisi Visual Pada Film “Sang Prawira” - Irham Setiawan; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Film is a mass communication medium that is very popular with the public. Interesting techniques are needed to increase the appeal of a film. One of the deep focus techniques in the film "Sang Prawira" by Ponti Gea is the deep focus technique. In the film "The Prawira" by Ponti Gea, there are several scenes where all the objects in the frame remain sharp and clear, whether they are close to the camera or far away. These scenes made researchers interested in examining the film "The Prawira" by Ponti gea. The research method used is a descriptive qualitative method. The research results show that the deep focus camera focusing technique is quite rarely used. Based on this research, it can be concluded that the film "Sang Prawira" by Ponti Gea uses the deep focus technique when you want to focus the audience's view on an object..